The Evolution, Achievements, And Prospects Of The Chinese School Of International Relations Theory - Dongqian, Zhao (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
Over the past fifty years, the discipline of International Relations in China has undergone continuous evolution. Chinese scholars have transitioned their focus from translating, introducing, and disseminating Western theories to delving into the creation of an international relations theory uniquely shaped by Chinese characteristics. While progress has been made in formulating a distinct Chinese international relations theory, there are still areas of inadequacy that require attention. This article aims to critically examine the theoretical development and accomplishments of the "Chinese School" in International Relations theories while also presenting its perspectives on the future direction of International Relations theories in China.
Keywords: International Relations Theory